Moderating Role of Board Composition on the Relationship between Environmental Disclosure and corporate performance of Nigerian manufacturing Quoted Companies - Gwar, Stephen; A. Angahar, Paul; Iorpev, Luper (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study is to ascertain the moderating effect of board composition on the relationship between environmental disclosure and corporate performance. Secondary data collected from the published annual reports and accounts of the selected listed manufacturing companies in Nigeria. The study made use of forty-five (45) manufacturing quoted on the Nigerian Exchange Group (NGX) and covers a period of ten (10) years ranging from 2013-2022. Agency theory is used as the foundational theory. Descriptive statistics, correlation and regression techniques were used to analyze the data. The findings of the study show that there is a significant effect of environmental disclosure on ROA of listed manufacturing companies in Nigeria. The study further revealed that board composition significantly moderates the relationship between environmental disclosure and financial performance of the sampled manufacturing companies listed on the NGX. The study recommends for an effective/efficient board composition in companies which will lead to more robust environmental disclosures, thus have a significant effect on corporate performance of companies.